MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DENGAN MENERAPKAN MODEL DAN MEDIA PEMBELAJARAN DI SEKOLAH - Hanifah, Elsa Syadza; Hidayati, Hidayati; Nurtina, Nurtina (Jurnal MIPA dan Pembelajarannya, 2024)
The research aims to foster interest in learning physics by utilizing interesting learning models and media, such as problem-based learning and discovery learning models, as well as media such as Student Worksheets (LKPD), E-modules, and animated videos. The subjects used in this research were 33 students of class XI F 8 SMA Negeri 13 Padang, while the subject of action was the physics teacher in that class. Data is collected through test techniques. This research was carried out in two stages, each stage consisting of design, action, observation, and reflection. The first stage applies a problem-based learning model, while the second stage uses a discovery learning model. The research results show that applying the two appropriate learning models and media can improve physics learning outcomes for class F8 students at SMA Negeri 13 Padang. This was realized by an increase in the average student academic results from before the action of 71.4, then in Stage 1 it reached 79.1, and finally, in Stage 2 it reached 90.1.